The dawn of everything : a new history of humanity - Graeber, David; Wengrow, D. (Allen Lane, 2021)
"A trailblazing account of human history, challenging our most fundamental assumptions about social evolution-from the development of agriculture and cities to the emergence of "the state," political violence, and social inequality-and revealing new possibilities for human emancipation"--